Printed multiple input multiple output antennas powered by passive metamaterial and defected ground for diverse sixth generation applications - Shahanawaz Kamal; Padmanava Sen (Scientific Reports)
Abstract The evolution of 6th generation (6G) wireless technology has become imperative due to the exponential growth of wireless devices and applications. In a macro-cellular scenario, the 6 GHz electromagnetic spectrum is projected to be the framework for 6G commencement. However, the main obstacles that inhibit their potential at the physical layer are the fabrication intricacies entailed in comprehending high port isolation ( $$|S_{21}|$$ ) and other key performance indicator (KPI) of compact printed multiple-input-multiple-output (MIMO) antennas. Subsequently, to overcome these impediments, six novel meander line-based MIMO antennas ( $${#1α ,#1κ -#5κ }$$ ) have been introduced for diverse 6G use cases, including internet of things, extended reality, artificial intelligence, vehicle-to-everything, unmanned aerial vehicle, and device-to-device integrated sensing and communications. Furthermore, two unique passive metamaterial structures of square ring ( $${α }$$ ) and shorting pins ( $${κ }$$ ) have been studied for attaining an electromagnetic bandgap (EBG). Their performance were investigated by means of numerical simulations and validated through measurements conducted within the anechoic chamber. Meticulous strategies for accomplishing impedance matching, circularly polarization (CP), and high $$|S_{21}|$$ values have been presented. Each of the proposed MIMO antennas employed dual radiators, a defected ground, and an EBG structure to exhibit $$|S_{21}|$$ of $$\gtrapprox $$ 21 dB, quasi-isotropic CP, and other desirable KPI of MIMO antennas. Their assembly possessed a low-profile of 0.03 free-space wavelength ( $$λ _0$$ ) and an area of 1.1 $$λ _0$$ $$× $$ 1.1 $$λ _0$$ , thus being preferable for cost-effective compact terminals. During the measurements, each prototype yielded one or more remarkable MIMO antenna KPI in the 6 GHz band. Particularly, $$MIMO^{#1α }$$ enabled filtered bandwidth (BW) of 8.84% and modest gain (G) of 6.4 dBic, $$MIMO^{#1κ }$$ attained high G of 7.1 dBic and enhanced efficiency ( $$η $$ ) of 87%, $$MIMO^{#2κ }$$ yielded high $$η $$ of 94%, $$MIMO^{#3κ }$$ established notable radiation pattern with fair G of 5.8 dBic, $$MIMO^{#4κ }$$ provided filtered BW of 9.69% and prominent $$η $$ of 93%, and $$MIMO^{#5κ }$$ featured wide axial ratio (AR-BW) of 60.63%. Furthermore, all antenna measurements demonstrated good MIMO performance with envelope correlation coefficient and diversity gain of <0.2 and $$≈ $$ 10 dB, respectively. The novelty of this work lies in the radiator and ground designs, as well as the accomplishment of numerous KPI that surpass state-of-the art MIMO antennas.